Effectiveness of the IDEFICS intervention on objectively measured physical activity and sedentary time in European children. (December 2015) - Verbestel, V.; De Henauw, S.; Barba, G.; Eiben, G.; Gallois, K.; Hadjigeorgiou, C.; Konstabel, K.; Maes, L.; Mårild, S.; Molnár, D.; Moreno, L. A.; Oja, L.; et al.
Summary: Background: This paper reports on the effectiveness of the prevention of dietary‐ and lifestyle‐induced health effects in children and infants (IDEFICS) intervention on objectively measured physical activity (PA) and sedentary time (ST) in 2‐ to 9.9‐year‐old European boys and girls. Methods: The intervention was evaluated after 2 years through a non‐randomized cluster‐controlled trial in eight European countries (one control and one intervention community per country). All children in the intervention group received a culturally adapted childhood obesity prevention programme through the community, schools/kindergartens and family. A random sub‐sample of children participating in the IDEFICS study wore an accelerometer at baseline and follow‐up for at least 3 days ( n  = 9, 184). Of this sample, 81% provided valid accelerometer data at baseline ( n  = 7, 413; 51% boys; 6.21 ± 1.76 years; boys: 617 ± 170 cpm day −1 ; girls 556 ± 156 cpm day −1 ) and 3, 010 children provided valid accelerometer data at baseline and during the follow‐up survey 2 years later. Results: In boys and girls, no significant differences in PA and ST were found between intervention and control groups over 2 years. Strong temporal effects were found in the total sample of boys and girls: the percentage of time spent in light PA per day decreased by 4 percentage points in both boys and girls between baseline and follow‐up (both: p  < 0.001), while time spent in ST per day increased by 4 percentage points in both sexes over time (both: p  < 0.001). Percentage of time spent in moderate‐to‐vigorous PA per day remained stable over time in boys and girls. Conclusion: Despite the socio‐ecological approach and implementation of a culturally adapted intervention in each country, no effects of the IDEFICS intervention were found on children's objectively measured PA and ST. Behavioural interventions for children may need to enhance specificity and intensity at the family level using other behaviour change techniques and more direct strategies to reach parents. © 2015 World Obesity